Keterkaitan antara Pola Keterampilan Berpikir dengan Penguasaan Konsep Siswa pada Pembelajaran Strategi Metakognisi Berbantuan Thinking Map - Puspitasari, Dyne Rizki; Yuliati, Lia; Kusairi, Sentot (Department of Physics, Sebelas Maret University, 2014)
The purpose of this research is to analyze relationship between thinking skill pattern and students’ conceptual acquisition on metacognitive strategy assisted by thinking map. This mixed method research (embedded experimental design) was conducted at junior high school students and used conceptual acquisition test (posttest) and observation paper. The observation paper was used to analyze students’ thinking skill pattern by using thinking map. The result of this research showed that students who had high thinking skill pattern reachedhigh conceptual acquisition score too. This physics conceptual acquisition score showed students’ cognitive process grade. Conclusion of this research is the relationship between thinking skill pattern and junior high school students’ physics conceptual acquisition is exist.